(g-h)(x) = 2x+1 -(<span>x-2)
</span>(g-h)(x) = 2x+1 - x + 2
(g-h)(x) = x + 3
Answer: B aka (3’2) + (3’2)
Step-by-step explanation:
I got it right on Edge 2021, good luck! Also if right, can you please mark Brainliest?
find 1/2 then add the two base the multiply the h and divide by two
Answer:
a. has one solution
b. infinite solution
Step-by-step explanation:
a.
2(x - 1) + 6 = 4x - 22
2x - 2 + 6 = 4x - 22
2x - 4x = 2 - 6 - 22
-2x = -26
x = 26/2
x = 13
b.
6(2x + 1) – 2 = 12x + 4
12x + 6 - 2 = 12x + 4
12x - 12x = 4 + 2 - 6
0 = 0
Answer:
1.315%
Step-by-step explanation:
Given:
Prices:
Year 1 =old price =$95
Year 2 = new price = $96.25
The inflation rate is the difference in price between two Given period :
Inflation rate :
(Change in price / old price) * 100%
((New price - old price) / old price) * 100%
((96.25 - 95) / 96) * 100%
= (1.25 / 95) * 100%
= 0.0131578 * 100%
= 1.315%